Ijtihad Syaikh Nawawi Al-Bantani dalam Living Al-Qur’an dan Sunah - Nur Mizab; Wahid Rozaq Raharjo; Arsan; Muhammad Askin; Faldin Salisu (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2025)
The Ijtihad of Shaykh Nawawi Al-Bantani in the context of the Living Al-Qur'an and Sunnah makes an important contribution in enriching the understanding and practice of Islamic teachings in Indonesia. As a great scholar, Shaykh Nawawi developed a deep understanding of religious texts, while at the same time linking them to social dynamics and the needs of society at his time. His ijtihad does not only focus on theoretical understanding, but also emphasizes the relevance and application of the teachings of the Qur'an and Sunnah in everyday life. In his work, Shaykh Nawawi succeeded in connecting classical scientific traditions with contemporary contexts, making Islamic teachings more alive and adaptable to ever-evolving social life. Through this approach, Shaykh Nawawi Al-Bantani's ijtihad makes an important contribution to an understanding of Islam that is inclusive, progressive and in line with the demands of the times.